NILAI-NILAI GOTONG ROYONG PADA ACARA PERNIKAHAN DI DESA PINANG SEBATANG TIMUR KECAMATAN TUALANG KABUPATEN SIAK - Widia Elsya Susanti; Mita Rosaliza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The culture of mutual cooperation is not new in human civilization, mutual cooperation in the sense that it is actually carried out by a group of residents in an area who come to help or offer their strength without strings attached or voluntarily help together. The progress of the times causes changes in each individual such as behaving individuality, These changes show that the community has shown the low values of social solidarity, especially in mutual cooperation in celebration or disaster events. However, in Pinang Sebatang Timur Village, the values of mutual cooperation are still found in the community. The formulations of the problem that being discussed in this research are as follows: how is the value of mutual assistance in the community of Pinang Sebatang Timur Village, Kecamatan Tualang, Siak. Research purposes to know the values of mutual cooperation contained in the wedding ceremony and to find out the value of reciprocity, the value of sincerity, the value of togetherness, the value of kinship in the wedding ceremony. The subjects of this study were 7 people consisting of 5 parents whose children held a wedding, 1 Zulham (RT head), and 1 Maruli (elder person). The technique of determining the informants used was purposive sampling. . The method used is a qualitative research method. The theory used is Fukuyama's theory of social capital. The results of the study can be concluded that the community still applies the values of mutual cooperation such as applying the values of togetherness, kinship, reciprocity, and sincerity. Keywords : Mutual cooperation, Weddings